2021
DOI: 10.1021/acs.inorgchem.1c01539
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) Diphosphine Complexes with Mercapto Ligands That Inhibit Topoisomerase IB and Suppress Tumor Growth In Vivo

Abstract: Ruthenium­(II) complexes (Ru1–Ru5), with the general formula [Ru­(N-S)­(dppe)2]­PF6, bearing two 1,2-bis(diphenylphosphino)­ethane (dppe) ligands and a series of mercapto ligands (N-S), have been developed. The combination of these ligands in the complexes endowed hydrophobic species with high cytotoxic activity against five cancer cell lines. For the A549 (lung) and MDA-MB-231 (breast) cancer cell lines, the IC50 values of the complexes were 288- to 14-fold lower when compared to cisplatin. Furthermore, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…It is worth pointing out that the arene ruthenium complexes which have been investigated as promising anticancer drugs [33–35] can be involved in the disruption of the cellular redox homeostasis via NADH transfer hydrogenation, as well as GSH metal thiol binding and oxidation [36] . Conversely, only few studies have been reported on the use of diphosphine ruthenium hydrogenation catalysts as efficient anticancer systems [37–40] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth pointing out that the arene ruthenium complexes which have been investigated as promising anticancer drugs [33–35] can be involved in the disruption of the cellular redox homeostasis via NADH transfer hydrogenation, as well as GSH metal thiol binding and oxidation [36] . Conversely, only few studies have been reported on the use of diphosphine ruthenium hydrogenation catalysts as efficient anticancer systems [37–40] …”
Section: Introductionmentioning
confidence: 99%
“…[36] Conversely, only few studies have been reported on the use of diphosphine ruthenium hydrogenation catalysts as efficient anticancer systems. [37][38][39][40] Herein we report the isolation of the cationic enantiomer complexes [RuX(CO)(PP)(phen)]Y (X, Y = carboxylates, thioacetate, PP = (R,R)-or (S,S)-Skewphos) [21] and their behaviour with (S)-cysteine and GSH via formation of aquo complexes. Remarkably different and very promising cytotoxic activity toward several cell lines has been observed for the couples of enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…2b); this was also reported earlier by Batista et al in [Ru(dppe) 2 (N–S)]PF 6 complexes, (where N–S = mercapto ligands). 22 Thus, the four P-atoms in two dppe ligands were chemically and magnetically non-equivalent in [Ru II (dppe) 2 (5-FU)](PF 6 ) ( Ru-DPPE-5FU ) as also evident from the crystal structure. A characteristic 31 P heptet signal around −143 ppm also confirmed the presence of PF 6 − as a counter anion.…”
Section: Resultsmentioning
confidence: 89%
“…Studies by Velozo-Sá et al 54 showed that ruthenium( ii ) complexes with the formula [Ru(pymS)(dppm) 2 ]PF 6 and [Ru(pymS)(dppe) 2 ]PF 6 , where pymS = 2-mercaptopyrimidine anion, were cytotoxic to both A549 and MDA-MB-231 tumor cells, with SI close to 5 and 10, respectively. Ribeiro et al 55 investigated ruthenium( ii ) complexes bearing five mercapto ligands with the general formula [Ru(N-S)(dppe) 2 ]PF 6 . Among the five cancer cells line examined by these authors, the complexes were selective toward the A549 and MDA-MB-231 cell lines when compared to MRC-5, a non-tumor cell line.…”
Section: Resultsmentioning
confidence: 99%